G385(P) Leptin effect on neurocognitive and motor functions in juvenile rats with premature brain damage model on 2 days old neonates. (24th May 2017) - Feng, E; Jiang, Prof
Abstract : More and more babies are born preterm, and most of them could be saved, but many of the survivors face lifelong disabilities, including learning disorder and visual and hearing problems. Unclear mechanisms of premature brain damage lead to the underlying safety and reliable treatment issues. Recently, scientists found that biological effects of leptin on non-hypothalamus area were such as learning and memory, cognitive function and neuroprotective effect. Therefore, we aimed to determine whether the neuroprotective effect appears on developing brain of very early preterm. Combining capture-resistance experiment, suspension experiment, open field test and Morris water maze test, we observed the effects of neurocognitive and motor function items by lepin in premature brain damage rats from 2 days postnatal to 21 days juvenile rat. Univariate and multivariate analysis (using multiple linear regression model) showed leptin alleviate the spatial memory impairment of premature brain damage, independent from gender and weight. These findings have important implications for our standing of leptin neuroprotective effects on preterm with brain damage.